Pengaruh Dosis Trichokompos dan Pupuk NPK Terhadap Pertumbuhan Bibit Rotan Jernang (Daemonorops draco Blume.) di Pembibitan - Irawan, Bambang; Neliyati, Neliyati; Ramadhan, Febri (Jurnal Silva Tropika, 2018)
Jernang (Daemonorops draco) is one of the most important species belongs to Palmae. It produces the valuable resin that internationally recognized as â€œdragon bloodâ€. The dragon blood is used for various products such as medicines, cosmetics and other uses as natural colors. However, the knowledge on the silviculture of jernang both in the nursery and plantation is still very limited. Mostly, the people collect the dragon blood resin from the wild. Due to this reason research on the effects of tricho-compost and NPK Fertilizer to the growth of Jernang seedling had been conducted. Completely Randomized Design with three replications and two factors of treatments namely tricho-compost and NPK Fertilizer dosages had been applied. The tricho-compost treatments consisted of three levels namely 0 g of tricho-compost; 250 g tricho-compost/seedling and 500 g trciho-compost per seedling while the NPK fertilizer consisted of 0 g NPK/seedling, 3 g NPK/seedling, 6 g NPK/seedling, 9 g NPK/seedling and 12 g NPK fertilizer/seedling. The data were analyzed using Analysis of Variance (Anova); and Duncan Multiple Range Test (DMRT) with the level of confidence of 95%. The results showed that the interaction between tricho-compost and NPK fertilizer was not significantly different as well as the results of each single treatment Further analysis using DMRT also revealed the same results were there was no significantly different among levels of treatments to the growth of jernang seedling.